Enterprise Interoperability : Research and Applications in Service-oriented Ecosystem (Proceedings of the 5th International IFIP Working Conference IWIE 2013). - Zelm, Martin (Wiley-ISTE, 2014)
In a fast changing global economy governed by Enterprise Services and the Future Internet, enterprises and virtual factories will self-organize in distributed, interoperable, innovation Ecosystems where the issues of Enterprise Interoperability need to be solved in a multi-view of information, services and processes throughout Enterprise Networks. The book constitutes the proceedings of five workshops co- located with the Fifth IFIP Working Conference IWEI 2013. It contains the presented peer reviewed papers and summaries of the workshop discussions.Complementing the IWEI Conference program, th.